EKSPRESI PINOPODA PASIEN ENDOMETRIOSIS KAJIAN POLIMORFISME GENA ALPHA V INTEGRIN, BETA 3 INTEGRIN, HOMEOBOX A-10 DAN EKSPRESI GENA ALPHA V BETA 3 INTEGRIN DAN HOMEOBOX A-10 - , Pinda Hutajulu, dr., Sp.OG ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Endometriosis is a gynecological disease that is often found in women of reproductive age with an incidence of 5-10%. Endometriosis decrease endometrial receptivity interfering with the development of oocytes and embryos and disrupting the function of reproductive organs, which in turn reducing fertility. Endometrial receptivity is characterized by pinopodes that s are one marker of endometrial receptivity and implantation process begins with the appearance of pinopodes. Development of pinopodes is regulated by several genes such as HOXA10 and ITGAVB3 in which their expression increased at the time the window of implantation. The objective of this study is to asses the association of genomic faktor, expression of proteomic and pinopods expression as a marker of endometrial receptivity. Design of this this study was a Case Control Study to test the hypothesis of the cause of infertilitas in endometriosis. The result of this study indicate that number and the scores of pinopodes in the endometriosis were lower than those in the control. Menstruation day 19 -20 was the date with the highest number and scores of pinopodes. The low number and scores of Pinopodes interfered with the apposition process. Variance 2 in HOXA10 gena in exon 2 bp 55 found nucleic acid change adenin to timin (A>T) with change in amino acid Serine to Cystein(SER 19 CYS) in 12 cases of endometriosis (38%) and no found in control.The expression of HOXA10 in the endometriosis was lower than that in the control The low expression of HOXA10 interrupted the process of apposition, dhesion, and decidualization. Polymorphism of ITGAV genes in the endometriosis was higher than that in the control. ITGAV gene polymorphism in the endometriosis was found at 40.7%. and 21 % in control. It can be concluded that there was a need for endometrial biopsy to see the expression of pinopodes and HOXA10. and the change of time on the embryo transfer to obtain the success rate of implantation.